2006
DOI: 10.1111/j.0307-6946.2006.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification in the spatial distribution of the beech scale insect (Ultracoelostoma assimile) inNothofagustree canopies in New Zealand

Abstract: Abstract.  1. The degree of infestation by New Zealand sooty beech scale insects (Ultracoelostoma assimile, Homoptera: Margarodidae) varies dramatically among adjacent southern beech trees (Nothofagus spp., Fagaceae), but has previously been assumed to be uniformly or randomly distributed within individual host trees. In this study, a full‐census survey was conducted from ground level to canopy level on 14 naturally occurring, canopy‐dominant red beech (Nothofagus fusca) trees (size range 38.7–107.6 cm diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In New Zealand, Wardhaugh et al (2006) showed that the density of the sessile bark-dwelling phloem-feeding scale insect Ultracoelostoma assimile (Margarodidae) was higher on branches in the canopy than low on the trunks of Nothofagus fusca (Fagaceae) trees. The authors suggest that vertical stratification in U. assimile is probably a function of bark thickness, which is vital to locating an appropriate settlement site.…”
Section: (1) Vertical Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, Wardhaugh et al (2006) showed that the density of the sessile bark-dwelling phloem-feeding scale insect Ultracoelostoma assimile (Margarodidae) was higher on branches in the canopy than low on the trunks of Nothofagus fusca (Fagaceae) trees. The authors suggest that vertical stratification in U. assimile is probably a function of bark thickness, which is vital to locating an appropriate settlement site.…”
Section: (1) Vertical Stratificationmentioning
confidence: 99%
“…Thin bark does not provide enough crevices, which are preferentially colonised (McAllum, 1992), and if the bark is too thick, the insect's stylet cannot reach the phloem elements. Indeed, the lower trunks of smaller trees (10-30 cm diameter at breast height), which are approximately the same diameter as the heavily infested branches of large trees, also harboured high densities of U. assimile (Wardhaugh et al, 2006), indicating that vertical stratification was dependent upon resource accessibility/availability.…”
Section: (1) Vertical Stratificationmentioning
confidence: 99%
“…For example, bees feed on honeydew, sap and other sugar sources in the absence of flowers (Elton, 1966) and the importance of honeydew to the longevity and fitness of hymenopteran parasitoids has been particularly well documented. Honeydew is probably more readily available high in the forest canopy (Moran and Southwood, 1982;Wardhaugh et al, 2006;Nickel, 2008), likely influencing the distributions of associated arthropods. For example, Ulyshen et al (2010b) found bees to be much more abundant high in the canopy than near the forest floor in the United States, especially in mid-summer when flowers were absent from the canopy and scarce near the ground.…”
Section: Sugarsmentioning
confidence: 99%
“…Wardhaugh et al, 14 reported greater scale abundance in elevated side branches of Nothofagus forests and briefly discussed possible determinants. However, they did not directly assess the role of biological control.…”
Section: Spatial Heterogeneitymentioning
confidence: 99%